Bubble-wake interactions of a sliding bubble pair and the mechanisms of heat transfer. (May 2017) - O'Reilly Meehan, R.; Donnelly, B.; Nolan, K.; Murray, D.B.
Highlights: Experimental investigation of bubble-wake interactions for a sliding bubble pair. Interactions studied using PIV, high-speed video and IR thermography. Trailing bubbles experience significant wake-induced motion & shape changes. Local convective heat flux enhancement of 8 times free convection observed. Trailing bubble can also momentarily decrease local convective heat flux levels. Abstract: An experimental investigation is reported for the bubble-wake interactions that occur between an in-line air bubble pair sliding under an inclined surface in quiescent water. Three experimental techniques are utilised to study this flow: time-resolved particle image velocimetry (PIV), a new edge-based bubble tracking algorithm incorporating high speed video and high speed infrared thermography. These techniques allow for a novel characterisation of sliding bubble-wake interactions in terms of their associated fluid motion, the fluid-induced changes in the trailing bubble interface and the resulting surface convective heat transfer. As these interactions are ubiquitous to multiphase flows, such knowledge is pertinent to many industrial applications, including the optimisation of two-phase cooling systems. This work has revealed that for an intermediate bubble size, in-line bubble pairs adopt a configuration in which their paths are 180° out of phase. Upon entering the fluid shed from the near wake of the leading bubble at each local extremum, the trailing bubble is accelerated both in the direction of buoyancy and in the spanwise direction corresponding to that of the shed fluid structure. This causes significant, high-frequency changes in the interface of the trailing bubble, which recoils and rebounds during this interaction. Surface heating adds further complexity to the bubble-wake interaction process due to the disruption of the thermal boundary layer at the surface. It is found that the trailing bubble can momentarily decrease local convective heat transfer levels by displacing the cool fluid introduced to the surface by the leading bubble. However, the amplified fluid mixing and local heat transfer enhancement of 7–8 times natural convection levels observed at the trailing bubbles mean that the net effect of the trailing bubble is to enhance convective heat transfer.